1971
DOI: 10.1126/science.173.3997.652
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Activity Related to Short-Term Memory

Abstract: Nerve cells in the monkey's prefrontal cortex and nucleus medialis dorsalis of the thalamus show changes of firing frequency associated with the performance of a delayed response test. Most cells increase firing during the cue presentation period or at the beginning of the ensuing delay; spike discharge highler than that in intertrial periods is present in some cells throughout the delay. These changes are interpreted as suggestive evidence of a role of frontothalamic circuits in the attentive process involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
1,181
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,864 publications
(1,251 citation statements)
references
References 13 publications
64
1,181
2
4
Order By: Relevance
“…This is exactly what has been reported now several times in unit recordings in the PFC of monkeys [5][6][7]28,33,39]. A few event-related fMRI studies have varied the length of the retention delay up to 24 s and have reported that the DLPFC activity does indeed span the entire delay [34 -37].…”
Section: Memory Load Effectssupporting
confidence: 76%
See 2 more Smart Citations
“…This is exactly what has been reported now several times in unit recordings in the PFC of monkeys [5][6][7]28,33,39]. A few event-related fMRI studies have varied the length of the retention delay up to 24 s and have reported that the DLPFC activity does indeed span the entire delay [34 -37].…”
Section: Memory Load Effectssupporting
confidence: 76%
“…Neurophysiological studies of monkeys [5,6,8,25,28] and more recently event-related fMRI studies of humans [33 -37] have recorded persistent activity during retention intervals of delayed response tasks from the DLPFC (Fig. 2).…”
Section: Persistent Delay-period Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons in frontal and parietal cortex show slow dynamics, including persistent and ramping activity, related to motor planning [1][2][3][4] , action timing 5,6 , working memory [7][8][9][10] and decision making [11][12][13] . Neurons have intrinsic time constants on the order often milliseconds 14 .…”
Section: Introductionmentioning
confidence: 99%
“…At the neural level, it is often assumed that lateral prefrontal cortex (PFC) plays a critical role in the storage and maintenance of visual information. In line with this view, monkey single-neuron recording studies have demonstrated that PFC neurons are activated in a sustained fashion during the delay period of working memory tasks (e.g., Fuster & Alexander, 1971). While such observations suggest, that PFC might be the primary locus for the temporary storage of task-relevant information for future use (e.g., Goldman-Rakic, 1990), more recent studies have cast doubt on this hypothesis (see Postle, 2006;D'Esposito, 2007, for reviews).…”
Section: Introductionmentioning
confidence: 79%